A Review on Quantum Computers and Machine Learning - Padmalatha, E; Sailekya, S (International Journal of Computer Sciences and Engineering, 2025)
Pattern can be learned from existing data to provide sense to the previously unknown data, this is possible only with the help of Machine learning. As part of both artificial intelligence and statistics, machine learning algorithms process large amounts of information. Machine learning refers to usage of computers to infer data based on knowledge. In the big data analysis huge amount of update data should be deal with the highly sophisticated machine learning algorithms . Quantum computing may improve classical machine learning algorithms if we deal with big data. The quantum computer works on the principle of translating stochastic methods into the language of quantum theory. This paper is focusing on the brief review on quantum computers and machine learning.